Serum biomarkers in Duchenne muscular dystrophy: a leap toward precision diagnostics - Matovu, Daniel (European Journal of Translational Myology, 2025)
I was interested to read the article by Dowling et al.1 in the European Journal of Translational Myology, where the authors provide a comprehensive review of serum biomarkers for Duchenne Muscular Dystrophy (DMD), a devastating early-onset muscle wasting disease. The emphasis of research on liquid biopsy-based approaches, with the application of Mass Spectrometry (MS)-based proteomics for the identification of novel biomarkers like carbonic anhydrase CA3, fatty acid binding protein FABP3, and titin fragments, represents a revolutionary step towards minimally invasive diagnostics. As a neurologist and clinical pharmacologist working in Uganda, where diagnosis of DMD is delayed owing to the limited access to invasive tests, I find the prospects of these biofluid-based markers not only intriguing but also of immense worth in advancing precision medicine in resource-poor settings. [...]